The Impact of Patent Applications in the Context of the ESG Model at World Level - Angelo Leogrande; Domenico Leogrande; Alberto Costantiello (ZBW - Leibniz Information Centre for Economics, 2023)
In the following article, we estimate the value of Patent Applications-PA in the context of the Environmental, Social and Governance-ESG model at world level. We use data from World Bank for 193 countries in the period 2011-2021. We found that PA is positively associated, among others, to “ CO 2 Emissions ” and “ Mammal Species Threated ”, and negatively associated among others to “ Hospital Beds ” and “ Research and Development Expenditures ”. Furthermore, we found that at aggregate level PA is negatively associated to each macro component of the ESG model i.e.: Environment, Social and Governance. Furthermore, we have applied eight different machine-learning algorithms for the prediction of the future value of PA. We found that the best predictive algorithm is the Simple Regression Tree in terms of minimization of MAE, RMSE and MSE and maximization of R-squared. The value of PA is predicted to growth by an average of 9.82% for the analysed countries.
Keywords: D7; D70; D72; D73; D78; 330; Political Processes; Legislatures; Corruption